CROSSING THE BOUNDARIES OF IDENTITY: A CONTEXTUAL HERMENEUTICS OF JOHN 4:7-15 IN THE CONTEXT OF MIGRATION THEOLOGY IN INDONESIA - Silaen; Junita Batubara (RADJA PUBLIKA, 2025)
This paper focuses on a contextual hermeneutical analysis of John 4:7–15 in relation to the theology of migration in Indonesia. Migration as a social phenomenon is a complex reality caused by various factors, such as economics, natural disasters, and developments in transportation and information technology that enable large-scale human mobility. In the Indonesian context, this phenomenon has been going on for a long time and continues to have significant social, cultural, and theological impacts. Through a contextual hermeneutical approach, this study seeks to explore the theological meaning of the conversation between Jesus and the Samaritan woman as a model for understanding contemporary theology of migration. The text of John 4:7–15 is understood as an event that transcends social, cultural, and identity boundaries. Jesus' dialogue with the Samaritan woman demonstrates an effort to break down discriminatory barriers between different groups and affirms the universal nature of love and salvation offered by Christ. In the context of the theology of migration in Indonesia, this passage reflects the values ​​of hospitality and inclusivity that form the basis for forming a community open to differences. Hospitality is understood not only as an attitude of welcoming the presence of strangers, but also as a reflection of God's love that erases the boundaries between